ISLAMIC BANKS AS A TOOL TO ACHIEVE SUSTAINABLE DEVELOPMENT - Emad Ali Meeloud Abdullah; PM. DR, Shahir Akram Hassan; PM. DR, Zakaria Bahari (International Journal of Accounting, Finance and Business, 2023)
This study aims to know the role of Islamic banks in achieving sustainable development by defining Islamic banks, their importance, objectives, and financing formulas. This study also defines sustainable development and its importance, goals, and dimensions. This paper intends to identify the most important ways that contribute to achieving sustainable development through three dimensions. They are social, economic, and environmental dimensions. The current study utilized the descriptive approach to know the role of Islamic banks in achieving sustainable development. This study finds that many investment methods in Islamic banks contribute to achieving sustainable development, including short-term ones such as Murabaha, Salam, and Mudarabah, and long-term ones such as Musharaka